2004
DOI: 10.1128/jcm.42.10.4620-4626.2004
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Transmission, Diversity, and Stability of Streptococcus mutans and Streptococcus sobrinus Genotypes in Brazilian Nursery Children

Abstract: The aim of this study was to perform a follow-up evaluation of the Streptococcus mutans and Streptococcus sobrinus colonization profile of children's oral cavities, which included the pattern of vertical transmission from mother to child, genotypic diversity, and stability of the strains. The subjects were 16 mother-child pairs, who were monitored for 20 months. Samples of saliva, tongue dorsum, alveolar ridge mucosa, and dental plaque from the children were collected bimonthly. Saliva samples from the mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
77
1
25

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 35 publications
14
77
1
25
Order By: Relevance
“…However, the present result was in agreement with earlier reports (Hirose et al 1993;Alaluusua et al 1996;Emanuelsson et al 2003;Napimoga et al 2004). It has been observed that the subjects harbor one to five distinct genotypes of S. mutans at different ages (Alallusuua et al 1996;Emmanuelsson et al 1998;Grönroos et al 1998;Klein et al 2004;Mattos-Graner et al 2001;Caulfield and Walker 1989;Kulkarni et al 1989;Kreulen 1997;Napimoga et al 2004). In the population examined, two individuals had only one genotype in the group caries-free, and only two had as many as five genotypes in the dental caries group.…”
Section: Discussionsupporting
confidence: 83%
“…However, the present result was in agreement with earlier reports (Hirose et al 1993;Alaluusua et al 1996;Emanuelsson et al 2003;Napimoga et al 2004). It has been observed that the subjects harbor one to five distinct genotypes of S. mutans at different ages (Alallusuua et al 1996;Emmanuelsson et al 1998;Grönroos et al 1998;Klein et al 2004;Mattos-Graner et al 2001;Caulfield and Walker 1989;Kulkarni et al 1989;Kreulen 1997;Napimoga et al 2004). In the population examined, two individuals had only one genotype in the group caries-free, and only two had as many as five genotypes in the dental caries group.…”
Section: Discussionsupporting
confidence: 83%
“…1, 2 and 3 demonstrated similar behavior for S. mutans and S. sobrinus derived from mixed cultures during the incubation period, even though they showed a higher number of CFU/mL in medium with sucrose added when compared to the other carbohydrates. These data confirm other studies such as those of Ashley and Wilson (2) (13), which determined sucrose to be the main substrate of the streptococcus mutans group. After a short incubation period (3 h), the mixed culture in medium containing sucrose or glucose (10%), fructose (10%) or glucose (5%) + fructose (5%) showed a greater number of CFU/mL of S. sobrinus compared to S. mutans.…”
Section: Discussionsupporting
confidence: 82%
“…Maternal consumption of xylitol gum has been shown to reduce MS colonization and caries significantly in their children up to 10 yrs old (Söderling, 2009). Although maternal transmission is widely accepted as a major route for MS colonization in children (Berkowitz and Jordan, 1975;Davey and Rogers, 1984;Li and Caufield, 1995;Alaluusua et al, 1996), studies have shown that fathers, other caregivers, and playmates are significant alternative sources (Mattos-Graner et al, 2001;Klein et al, 2004;Domejean et al, 2010). In the presence of both maternal and nonmaternal sources of MS transmission, it may be more effective to focus on the destination of the bacteria-the children-than on the various sources.…”
Section: Introductionmentioning
confidence: 99%